P6.01 IMPLANTABLE PULSE WAVE VELOCITY SENSOR - A. Domnich; J. Schaechtele (Artery Research, 2013)
In case of vascular weakness or thrombosis stents are implanted and brace vessels from the inside to assure the proper blood flow. A widespread method to monitor the state of blood vessels in terms of their stiffness and diameter is to measure the pulse wave velocity (PWV). The stiffer or the narrower a vessel is the higher is the pulse wave velocity. At present no diagnosis method exists to determine the state of the implanted stent directly and non-invasive. In case of a reasonable suspicion catheterization for precise diagnosis is required. The new approach developed at Fraunhofer IPA allows measuring the PWV locally, so it can be applied in shorter intervals. This approach is based on inductive coupling. It consists of two passive units integrated into the stent and an extra-corporal detection unit. The passive units consist of a capacitive pressure sensor and an air-coil (Fig.1). They form an oscillating circuit, the resonance frequency of which functionally depends on the local blood pressure. The extra-corporal detection unit consists of an excitation coil which generates an alternating magnetic field and a circuit for signal detection. The spreading pulse wave changes the resonance frequency of the passive oscillating circuits inside the vessel in such a way, that it crosses the frequency of the externally applied field while the pulse wave passes by (Fig. 2). The short resonance leads to a shift in the impedance measured at the excitation coil. As the distance between the two sensors is known the PWV can be determined. Figure 1Scheme of functional principle Figure 2Schematic pulse wave propagation